GeroEduca: Construção de um Programa Psicoeducativo para promover o envelhecimento saudável - Cristele Monteiro Pinto (2022)
The increase in longevity can be considered as one of the main successes of today's societies, although it implies great challenges in terms of public health. Psychoeducation programs aimed at the community of older adults are presented as a behavior change strategy, providing knowledge and tools for the adoption of healthier behaviors in everyday life and providing a feeling of greater control and autonomy of the health condition. This qualitative work documents the process of developing a psychoeducational intervention program (GeroEduca) on healthy aging. The process consisted of 7 steps: (1) Questionnaire to seniors and literature search; (2) Construction of the GeroEduca program - version 1; (3) Implementation of a pilot study with GeroEduca - version 1 with 12 adults with an average age of 73.6 years (SD = 7.5); (4) Analysis of the results of the pilot study regarding the participants' perceptions of the experiences lived in the program sessions, as well as on structural aspects, themes and activities; (5) Implementation of changes in the program based on the results: GeroEduca - version 2; (6) Conducting a focus group study, centered on GeroEduca (versions 1 and 2), with 6 professionals from the areas of social and human sciences and health; (7) Presentation of the final version of GeroEduca based on the results of the content analysis carried out on the data collected in the focus group interview. Of these 7 steps, only steps 4 to 7 were studied in the scope of this work. The GeroEduca program in its final version is composed of 18 sessions of 90 minutes each, and is organized into 8 thematic modules: (1) Aging; (2) Most common diseases in old age; (3) Health and promotion of healthy living habits; (4) Benefits of physical activity; (5) Healthy eating; (6) Social interaction; (7) Mental health and emotion regulation; and (8) Cognitive functioning. The iterative development of GeroEduca made it possible to align the program both with the characteristics of the target audience and with the professionals who will be able to implement it in a community context. GeroEduca is considered a promising tool for promoting active and healthy aging.